Material didático digital no ensino de Educação Física nos anos finais do Ensino Fundamental - Castro, Érico Roberto Duarte de (2022)
The current society uses digital information and communication technologies in the most varied sectors, reverberating both in Education and Information Science. School Physical Education, in turn, has been undergoing reformulations in its practice, which includes the need to make use of digital technologies in its teaching procedures, whose importance involves the adoption of well-founded strategies for the selection of digital teaching materials for the planning of classes, given the lack of textbooks in a systematic way in schools. In this context, this research aims to investigate how the organization of content available in digital repositories and digital curation actions can promote lesson planning by Physical Education teachers in the final years of elementary school, based on the experience of public schools in Maranguape-CE. This is action research, whose procedures involved: diagnosis, planning of a training action, execution of the training action, and evaluation. Bibliographic research was also carried out, aiming to investigate state of the art in research on the use of Digital Information and Communication Technologies (TDIC) in Physical Education classes at school, from 2015 to 2021. The results revealed, both from the bibliographic review and from the empirical research that: there is a lack of Physical Education textbooks aimed at the final grades of elementary school; few teachers feel empowered to build their lesson plans with the support of digital technologies; there is a demand for teacher training in the use of TDIC aimed at teachers in this area; knowledge about curation and digital repositories can help Physical Education teachers in how to manage the information sought for the planning of their classes. Thus, the more possibilities in continuing education focused on the curation of digital teaching materials and the availability of digital resources for the area of Physical Education teachers have, the more they will be able to contribute to a relevant teaching-learning process contextualized with the needs of the school community in which they participate.